The incredible book eating boy - Jeffers, Oliver (New York : Philomel Books, 2007)
Henry loves to eat books, until he begins to feel quite ill and decides that maybe he could do something else with the books he has been devouring.
"Oliver Jeffers presents the incredible book eating boy"--Dust jacket.
Die-cut cover and pages.
First published: London : HarperCollins, 2006.
Kirkus Review
2.2
K-3.
Keywords: Books -- Juvenile fiction; Food habits -- Juvenile fiction; Books -- Fiction; Food habits -- Fiction; Books -- Fiction; Eating customs -- Fiction; Picture books for children; Picture books for children